2018
DOI: 10.3390/ijerph15091945
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Awareness Campaign to Reduce Second Hand Smoke Among Disadvantaged Families—A Participatory M-Health Approach

Abstract: Children from disadvantaged families are particularly exposed to second hand smoke in their home environment. Using a mixed methods participatory approach, we aimed at identifying suitable media channels and appropriate content for a campaign increasing caregivers’ knowledge about the risks of second hand smoke (SHS) exposure for their children and appropriate measures for exposure reduction. In the first phase of the mixed method design, we evaluated knowledge and norms about children’s SHS and perceived barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Ferré et al (2010) also reported a move towards a community-led participatory research (CPPR) approach. The three European publications referred to participatory action research (PAR) [ 28 ], or a participatory approach in general, without defining the term precisely [ 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ferré et al (2010) also reported a move towards a community-led participatory research (CPPR) approach. The three European publications referred to participatory action research (PAR) [ 28 ], or a participatory approach in general, without defining the term precisely [ 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three of the ten publications included only descriptions of preliminary stages of participation, such as informing, listening, or involving the addressees [ 22 , 28 , 29 ]. Johnson-Shelton et al (2015) and Schäfer and Bär (2019) exclusively indicated forms of actual participation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of participatory design depends on roles (eg, informants and co-design) and game design elements (eg, game levels or challenges) [ 14 ]. However, to the best of our knowledge, few studies have followed a user-centered design approach in the design of mHealth apps for disadvantaged populations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%